SEPARATION AND IDENTIFICATION OF NAPHTHALENE,ACENAPHTHYLENE, PYRENE, BENZA ANTHRACENE AND1,3,2,4-DIBENZANTHRACENE - Shamar, J M (Al-Nahrain Journal of Science, 2018)
Reverse Phase High Performance Liquid Chromatography (RP-HPLC) was coupled with ultraviolet absorption sepectoscopy (UV) for separation and identification of Naphthalene, Acenaphthylene, Pyrene, Benza anthracene and 1,3,2,4-Dibenzanthracene.RP-HPLC was performed on an ODS-C18 column (150×4.6 mm I.D) using acetonitrile–buffer phosphate as mobile phase. UV absorption spectra of the elutes was detected in 254 nm, and studying the chromatographic variables include organic modifier ratio, PH, column temperature and concentration of buffer to maximize resolution and minimize separation time. the results showed that using mobile phase( 80:20) v/v acetonitrile:0.01M phosphate buffer solution at PH 6 with flow rate 1ml/min and column temperature 60 C° at wave length 254 nm would give ideal separation with good resolution. The separation time was (7.5) min.